Aluminum acrylate composition and method for producing same

JP7632935B1Active Publication Date: 2025-02-19ASADA KAGAKU IND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024182089
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-05-13
Filing Date
2024-10-17
Publication Date
2025-02-19
Estimated Expiration
2044-10-17

AI Technical Summary

Benefits of technology

【0008】 本発明のアクリル酸アルミニウム組成物は、pH3~10で安定性の良い水溶液の形態を有する。本発明のアクリル酸アルミニウム組成物は、幅広いpH域で安定であるので扱いが容易であり、しかも紙に塗工し重合させる簡便な方法で、強度向上かつ耐水性を改善することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632935000001
    Figure 0007632935000001
  • Figure 0007632935000002
    Figure 0007632935000002
Patent Text Reader

Abstract

An object of the present invention is to provide an aluminum acrylate composition in the form of an aqueous solution which can be applied to paper to improve its strength and water resistance and has excellent solution stability, and a method for producing the same. The present invention provides an aluminum acrylate composition which contains 1 to 35% by mass of aluminum acrylate and is in the form of an aqueous solution in the pH range of 3 to 10, Aluminum is 2 to 15 mass% calculated as Al2O3, 2 to 30% by mass of acrylic acid, 4 to 25% by weight of a hydroxy acid, and Alkaline content: 0 to 15% by mass The present invention provides an aluminum acrylate composition comprising:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention provides an aluminum acrylate composition mainly containing aluminum acrylate. The aluminum acrylate composition of the present invention has the form of an aqueous solution with good stability over a wide pH range of 3 to 10, and can be coated on paper and cured to improve its strength and water resistance. [Background technology]

[0002] Aluminum acrylate is used in healthcare and civil engineering and construction-related fields, such as the manufacture of water-absorbent resins and hydrous gels, or the manufacture of water-stopping and waterproof seals. It is also used as a processing agent for defibrating, adsorbing, flocculating, crosslinking, and improving physical properties such as strength of paper, pulp, and fibers. It is also used in a wide range of fields, such as surface treatment for improving adhesion and water resistance of metals, glass, pigments, rubber, nonwoven fabrics, and the formation of fine dispersions. However, aluminum acrylate is originally a powder that is poorly soluble in water and organic solvents, and its range of application is extremely limited, such as being dissolved under strong acid or strong alkali conditions, and there have been problems in applying it in many fields where it is required. In particular, in recent years, there has been a great need for high-performance paper as a substitute for resin materials due to environmental considerations. In such cases, materials that can be easily processed by coating to impart functions such as strength improvement and water resistance are required.

[0003] Japanese Patent Laid-Open No. 48-091012 (Patent Document 1) discloses a method for obtaining aluminum acrylate in the form of an aqueous solution by neutralizing aluminum sulfate or the like to obtain gel-like aluminum hydroxide, and adding acrylic acid to the gel. However, in practice, the aqueous solution of aluminum acrylate obtained is extremely unstable, and crystals of a basic salt that is poorly soluble in water are likely to form. Furthermore, if sulfate radicals remain, they form a complex salt with acrylic acid, which is easily stabilized in water, but the pH of the aqueous solution is extremely low at 1 to 2, making it difficult to handle.

[0004] In JP-A-03-131649 (Patent Document 2), an alkaline earth metal salt of acrylate is polymerized with a trivalent metal salt, and the trivalent metal salt is preferably water-soluble. Aluminum acrylate is also described along with aluminum sulfate, etc. However, as mentioned above, when an inorganic acid is contained, it is highly corrosive, and aluminum acrylate alone is insoluble in water. In addition, in Example 2 of Patent Document 2, a 30% aqueous aluminum acrylate solution is also described, but the ingredients and method are not specified, and the method is not reproducible, so it cannot be carried out. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Unexamined Patent Publication No. 48-091012 [Patent Document 2] Japanese Patent Application Publication No. 03-131649 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an aluminum acrylate composition in the form of an aqueous solution which can be applied to paper to improve its strength and water resistance and has excellent solution stability, and a method for producing the same. [Means for solving the problem]

[0007] That is, the present invention provides the following aspects: [1] An aluminum acrylate composition comprising 1 to 35% by mass of aluminum acrylate and in the form of an aqueous solution having a pH in the range of 3 to 10, Aluminum is 2 to 15 mass% calculated as Al2O3, 2 to 30% by mass of acrylic acid, 4 to 25% by weight of a hydroxy acid, and Alkaline content: 0 to 15% by mass 1. An aluminum acrylate composition comprising: [2] The aluminum acrylate composition according to [1], wherein the hydroxy acid is at least one selected from the group consisting of lactic acid, gluconic acid and glycolic acid. [3] The aluminum acrylate composition according to [1] or [2], wherein the hydroxy acid is supplied in the form of an aluminum hydroxy acid, and the ratio of the number of moles of hydroxy acid in the aluminum hydroxy acid (I) to the number of moles of Al2O3 calculated from the number of moles of aluminum in the aluminum hydroxy acid (II) is in the range of I / II = 1.0 to 2.5. [4] The aluminum acrylate composition according to [1] or [2], wherein the alkali component is at least one selected from the group consisting of monovalent alkali metals, ammonia, and water-soluble amines. [5] When the number of moles of aluminum in terms of Al2O3 in the aluminum acrylate composition is [A], the number of moles of hydroxy acid is [B], the number of moles of acrylic acid is [C], and the number of moles of an alkali component is [D], the following relational formula (1) or (2) is satisfied: (1) [B] / [A]=1.0~2.5, [C] / [A]=1.0~2.5, [D] / [A]=0, or (2)[B] / [A]=1.0~2.5, [C] / [A]=3.5~4.5, [D] / [A]=4.5~7.5 The aluminum acrylate composition according to [1] or [2], wherein the ratio is within any one of the ranges of the above. [6] The method for producing an aluminum acrylate composition according to [1] or [2], characterized in that an aluminum hydroxide gel is obtained by neutralizing an inorganic aluminum acid with an alkaline agent at a temperature of 0 to 40°C and a pH of 6 to 8, the aluminum hydroxide gel obtained is washed with water, and then a hydroxy acid is added to form an aluminum hydroxy acid. Thereafter, acrylic acid is added, and an alkali component is further added as necessary to adjust the pH to 3 to 10. [7] The method for producing an aluminum acrylate composition according to [6], wherein the alkaline agent is at least one selected from the group consisting of sodium aluminate, sodium carbonate, ammonia and water-soluble amines. [8] The method for producing an aluminum acrylate composition according to [6], wherein the hydroxy acid is at least one selected from the group consisting of lactic acid, gluconic acid and glycolic acid. [9] The method for producing an aluminum acrylate composition according to [6], wherein the alkali component is at least one selected from the group consisting of monovalent alkali metals, ammonia and water-soluble amines. Effect of the Invention

[0008] The aluminum acrylate composition of the present invention is in the form of an aqueous solution with good stability at pH 3 to 10. The aluminum acrylate composition of the present invention is easy to handle because it is stable over a wide pH range, and moreover, it is possible to improve the strength and water resistance of paper by a simple method of coating the paper and polymerizing it. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the present invention will be described in detail based on preferred embodiments, but the present invention is not limited to the following embodiments and various modifications are possible within the scope of the claims. In addition, in the present invention, the expression "numeric value 1 to numerical value 2" in a numerical range has numerical value 1 as the lower limit and numerical value 2 as the upper limit. It means a range including numerical value 1 and numerical value 2 at both ends, and is synonymous with "numerical value 1 or more and numerical value 2 or less." Furthermore, in the present invention, "aluminum acrylate composition" means a mixture in the form of an aqueous solution containing at least aluminum acrylate, and includes unreacted components added during production and aluminum reacted with acids other than acrylic acid in the form of monovalent to trivalent salts.

[0010] (Aluminum acrylate composition) In the aluminum acrylate composition of the present invention, aluminum acrylate is a compound having the chemical formula [(CH2=CHCOO)3·Al], and is contained in an amount of 1-35% by mass, preferably 2-33% by mass, and more preferably 2-30% by mass. If it is less than 1%, the effective amount of Al is insufficient, and if it exceeds 35%, the solubility is insufficient, causing precipitation and making the composition unstable. The amount of aluminum acrylate is calculated assuming that the aluminum acrylate has the chemical structure of the above chemical formula. In reality, the composition may have only one or two acrylic acids attached to the aluminum atom, but for the purpose of calculation, the above chemical formula, i.e., three acrylic acids attached to the aluminum atom, is considered.

[0011] The aluminum acrylate composition of the present invention maintains the form of an aqueous solution in the pH range of 3 to 10. This means that the aluminum acrylate composition is stable over a wide pH range. The pH range is preferably 3 to 9.5, more preferably 3 to 9. If the pH is less than 3, the composition is highly acidic, leading to problems in terms of corrosiveness and durability, and if the pH exceeds 10, the composition is unstable and its storage stability deteriorates.

[0012] The aluminum acrylate composition of the present invention contains aluminum in an amount of 2 to 15 mass %, preferably 2 to 14 mass %, and more preferably 2 to 13 mass %, calculated as Al2O3. The concentration of aluminum (Al) is expressed in terms of Al2O3. Aluminum exists as a compound with various anions, and in this field, aluminum (Al) is expressed in terms of Al2O3. The aluminum content is 2 to 15 mass % calculated as Al2O3. If the aluminum content is less than 2%, the effective amount of aluminum is insufficient, and if it exceeds 35%, the solubility is insufficient, causing precipitation and making the composition unstable.

[0013] The aluminum acrylate composition of the present invention contains 2-30% by mass of acrylic acid. If the amount of acrylic acid is less than 2% by mass, the composition is not sufficiently cured and the performance is insufficient, whereas if the amount of acrylic acid is more than 30% by mass, the composition is unstable and prone to precipitation. The amount of acrylic acid is preferably 2-28% by mass, more preferably 2-26% by mass. Although "acrylic acid" forms various compounds, the amount of "acrylic acid" in the compound, i.e., the amount of CH2CHCOOH, is calculated regardless of the compound form.

[0014] The aluminum acrylate composition of the present invention contains 4 to 25% by mass of hydroxy acid. If the amount of hydroxy acid is less than 4% by mass, the stabilizing effect of aluminum is insufficient and the composition becomes unstable, and if the amount of hydroxy acid is more than 25% by mass, the amount of stabilizer is too much and the physical properties are adversely affected. The amount of hydroxy acid is preferably 5 to 24% by mass, more preferably 6 to 23% by mass. Specifically, the hydroxy acid is one or more selected from lactic acid, gluconic acid, and glycolic acid. Although "hydroxy acid" forms various compounds, the amount of "hydroxy acid" in the compound is calculated regardless of the compound form. For example, in the case of lactic acid, the amount is calculated as the amount of CH3CH(OH)COOH.

[0015] The aluminum acrylate composition of the present invention contains 0-15% by mass of an alkali component. If the alkali component exceeds 15% by mass, the pH becomes too high and the solution tends to become unstable. The amount of the alkali component is preferably 0-14% by mass, more preferably 0-13% by mass. Specifically, the alkali component is one or more selected from monovalent alkali metals, ammonia, and water-soluble amines. The "alkali component" exists as various salt compounds in the aluminum acrylate composition, but regardless of the form of the salt compound, the amount of the "alkali component" in the compound is calculated. For example, if the alkali metal is sodium (Na), the amount of Na is calculated. If the alkali metal is ammonia, the amount of NH3 is calculated.

[0016] The aluminum acrylate composition of the present invention satisfies the following (1) or (2), where the number of moles of aluminum calculated as Al2O3 in the aluminum acrylate composition is [A], the number of moles of hydroxy acid is [B], the number of moles of acrylic acid is [C], and the number of moles of alkali is [D]: (1) [B] / [A]=1.0~2.5, [C] / [A]=1.0~2.5, [D] / [A]=0, or (2)[B] / [A]=1.0~2.5, [C] / [A]=3.5~4.5, [D] / [A]=4.5~7.5 The molar ratio in this formula means the total amount of components added to the production of the aluminum acrylate composition. Therefore, the molar number of aluminum is the total molar number of aluminum involved in the production of the aluminum acrylate composition, the molar number of hydroxy acid is the total molar number of hydroxy acid added during the production of the aluminum acrylate composition, and the molar number of alkali component is the total molar number of alkali component added during the production of the aluminum acrylate composition.

[0017] The appropriate range of the amount of components present in the aluminum acrylate composition is, in the case of (1) above, [B] / [A] = 1.0 to 2.5. If it is less than 1.0, precipitation and sedimentation are likely to occur, and if it exceeds 2.5, the amount of acrylic acid added is relatively small, resulting in difficulty in polymerization. [C] / [A] = 1.0 to 2.5. If it is less than 1.0, the amount of acrylic acid is small, resulting in weak polymerization, and if it exceeds 2.5, precipitation and sedimentation are likely to occur, which is not preferable. [D] / [A] = 0, and no alkali component is contained. Therefore, the above case (1) is a case in which no alkali component is added.

[0018] On the other hand, when the pH is adjusted with an alkaline component, it is the above case (2). In that case, [B] / [A] is in the range of 1.0 to 2.5. If it is less than 1.0, precipitation is likely to occur, and if it exceeds 2.5, the amount of acrylic acid added is relatively small, making it difficult to polymerize. [C] / [A] is in the range of 3.5 to 4.5. If it is less than 3.5, it is unstable and precipitation is likely to occur, and if it exceeds 4.5, it is undesirably strong acidity. [D] / [A] is in the range of 4.5 to 7.5. If it is less than 4.5, precipitation is likely to occur, and if it exceeds 7.5, the pH becomes too high and becomes unstable.

[0019] (Method of producing aluminum acrylate composition) The aluminum acrylate composition of the present invention is produced by adding a predetermined amount of acrylic acid to an aqueous solution of aluminum hydroxy acid, and then adjusting the pH to 3-10 by adding an alkali component as necessary.

[0020] First, an aqueous solution of aluminum hydroxy acid is synthesized by neutralizing inorganic aluminum acid and an alkaline agent in the presence of water as a solvent at a temperature of 0 to 40°C or less and at a pH controlled within a range of 6 to 8 to obtain an aqueous dispersion of aluminum hydroxide gel.

[0021] The inorganic aluminum acid may be aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum phosphate or various basic salts, and one or more of these may be used. The alkaline agent may be one or more of sodium aluminate, sodium carbonate, ammonia or water-soluble amines. The amount of inorganic aluminum acid and alkaline agent used depends on the H content in the inorganic aluminum acid. + The number of OH contained in the alkaline agent ー The neutralization is carried out within the range of neutralization equivalents where the number of is equal, but priority is given to control of the pH range described below.

[0022] The reaction is carried out at a temperature of 0 to 40°C or lower, and at a pH controlled in the range of 6 to 8. The reaction temperature is preferably 0 to 40°C, and more preferably 5 to 30°C. If the reaction temperature exceeds 40°C, the aluminum hydroxide gel is likely to deteriorate, and if the reaction temperature is below 0°C, the solvent water may freeze or the solution viscosity may increase, which is undesirable. The pH is 6 to 8, and preferably 6 to 7. If the pH is less than 6, the aluminum hydroxide gel may aggregate and solidify, and if it is higher than 8, the aluminum hydroxide gel may deteriorate.

[0023] The aluminum hydroxide gel obtained by the above reaction is washed with water, desalted, and then a hydroxy acid is added and dissolved by heating to form an aluminum hydroxy acid. By washing the aluminum hydroxide gel, impurities such as salts are washed and removed. Examples of solid-liquid separation devices capable of washing with water include, but are not limited to, a centrifuge and a single plate filter. The washed aluminum hydroxide gel is obtained in the form of a water-containing cake or an aqueous dispersion, and a hydroxy acid is added and dissolved by heating. The heating temperature is preferably 60 to 110°C, and preferably 70 to 110°C. If the temperature is lower than 60°C, it takes too long to dissolve the gel, and if the temperature exceeds 110°C, the solution boils and easily scatters, which is not preferable. The heating time is 0.5 to 15 hours, and preferably 1 to 8 hours. If the temperature is less than 0.5 hours, the gel is not sufficiently dissolved, and if the temperature exceeds 15 hours, the gel deteriorates and becomes difficult to dissolve, and it takes a long time, which is uneconomical. The obtained aqueous solution of aluminum hydroxy acid is filtered as necessary to obtain a clear solution. Examples of filtration devices include, but are not limited to, a cartridge filter and a pressure filter.

[0024] The hydroxy acid used to form the aluminum hydroxy acid aqueous solution includes monobasic acids such as lactic acid, gluconic acid, and glycolic acid, and is preferably lactic acid. The hydroxy acid may be one or more of these. In this case, the mole number (I) of the hydroxy acid and the mole number (II) of aluminum in the aluminum hydroxy acid calculated as Al2O3 are in the range of I / II=1.0 to 2.5, preferably 1.0 to 2.3, and more preferably 1.0 to 2.0. If the above I / II is less than 1.0, the solution is likely to solidify and is unstable, and if the I / II is more than 2.5, the solubility of the aluminum compound is reduced and the solution is likely to precipitate and is unstable.

[0025] The aluminum hydroxylate used in the present invention is preferably in the form of an aqueous solution, and the aluminum hydroxylate aqueous solution preferably has an Al2O3-equivalent concentration of 1 to 25% by mass, with a concentration of less than 1% by mass being uneconomical due to the low concentration, and a concentration of more than 25% by mass being highly viscous and difficult to handle. If necessary, the aluminum concentration in terms of Al2O3 can be adjusted by diluting with water.

[0026] Next, acrylic acid is added to the synthesized aqueous aluminum hydroxy acid solution to form an aluminum acrylate composition. The aluminum acrylate composition may have its pH adjusted by adding an alkali component as necessary. The reaction between acrylic acid and aluminum hydroxy acid is carried out at a temperature in the range of 0 to 40°C. If the temperature exceeds 40°C, the aluminum salt is easily hydrolyzed and becomes cloudy, which is not preferable. If the temperature is below 0°C, crystals are easily precipitated and it is uneconomical. The reaction temperature is preferably 0 to 35°C. Pressure control is not required throughout the reaction, and it can be carried out at normal pressure. At this time, filtration may be carried out as necessary from the viewpoint of deposits or removal of foreign matter.

[0027] The alkaline component used for adjusting the pH includes monovalent alkali metals, ammonia, and water-soluble amines, and is preferably an alkali metal or ammonia. These may be used alone or in combination of two or more. The pH of the resulting aluminum acrylate composition is preferably 3 to 10, and more preferably 3 to 9. The wide pH range of 3 to 10 ensures a wide pH range.

[0028] The aluminum acrylate composition of the present invention can also be made into a dry powder. The powder can be used as a solution by adding a predetermined amount of water when necessary to dissolve it. The drying temperature for obtaining a dried product is 20 to 200°C. If the temperature is lower than 20°C, it takes a long time to dry, which is uneconomical, and if the temperature exceeds 200°C, it is undesirable because it turns yellow or becomes cloudy when dissolved.

[0029] (Characteristics or Properties of Aluminum Acrylate Composition) The aluminum acrylate composition of the present invention has excellent storage stability without precipitation even at room temperature to 40°C for more than 3 months. The reason why the aluminum acrylate composition of the present invention has improved water solubility and storage stability is unclear, but it is believed to be due to the metal chelating action of the hydroxy acid. In an acidic region of less than 7 pH, the stability is greatly improved by not forming a complete salt with hydroxy acid and acrylic acid relative to the Al2O3-equivalent molar amount of aluminum, but leaving a certain amount of hydroxyl groups. In a neutral to alkaline region of pH 7 or more, even if the aluminum is completely neutralized with hydroxy acid and acrylic acid relative to the Al2O3-equivalent molar amount of aluminum, the chelating action is strong, so that the stability can be improved without precipitation.

[0030] (Coating solution of aluminum acrylate composition) The aluminum acrylate composition of the present invention can be applied to paper and cured with UV light to provide the paper with strength and water resistance against high humidity. The coating liquid often contains a base monomer and a polymerization initiator. Hydrophilic resins are often used as base monomers for functional coatings on paper because of their adhesion to the base paper, coatability, and environmental safety. However, there is a problem that strength is reduced due to the influence of humidity, and water resistance is weakened. The aluminum acrylate composition of the present invention can be added to a coating liquid and cured with UV light to improve the strength and water resistance of paper materials.

[0031] The base monomer of the coating liquid is, for example, an acrylic monomer, specifically a (meth)acrylate, more specifically a hydrophilic monofunctional or bifunctional (meth)acrylate. Examples of such (meth)acrylate monomers include polyethylene glycol di(meth)acrylate, polyethylene glycol mono(meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl acid phosphate, 2-(meth)acryloylmorpholine, methylenebisacrylamide, dimethylacrylamides, etc.

[0032] Coating fluids are often cured by photopolymerization. In the case of photopolymerizable coating fluids, a photopolymerization initiator is blended into the coating fluid. Common photopolymerization initiators such as acylphosphine oxides, α-hydroxyacetophenones, and α-aminoacetophenones can be used.

[0033] If necessary, other additives such as antioxidants, dispersants, thickeners, chain transfer agents, polymerization inhibitors, reinforcing agents, compatibilizers, adhesion agents, colorants, etc. may be appropriately added to the coating liquid.

[0034] (Example) The present invention will be described in more detail with reference to examples. The present invention should not be construed as being limited to these examples. In the examples, % and parts are based on mass unless otherwise specified.

[0035] Example 1 678.6g of water was added to a 3L separable flask and stirred at 200 rpm, and 314.7g of an aluminum chloride aqueous solution (Al2O3 equivalent = 10.0%) and 250.8g of a sodium aluminate aqueous solution (Al2O3 equivalent = 20.0%) were added thereto at the same time to obtain 1244.1g of an aluminum hydroxide gel dispersion. At this time, the temperature was 20-25°C and the pH was 6.5-7. The obtained gel dispersion was centrifuged at 2000 rpm x 1 minute with a centrifuge (Kansai Centrifugal Separator Manufacturing Co., Ltd. KBS-12), and the gel was washed three times with 4L of water, and then the gel was placed in a 1L separable flask, 90% lactic acid was added thereto, and the mixture was heated at 100°C for 2.5 hours to obtain 1500g of a basic aluminum lactate solution (Al2O3 = 8.4%, lactic acid / Al2O3 molar ratio: 2.0). 151.5 g of acrylic acid was added to this solution (temperature: 25° C.) to obtain an aluminum acrylate composition (aluminum acrylate 10.3%, pH=3.5). The obtained aluminum acrylate composition was stable without precipitation even after 3 months at 40° C.

[0036] Example 2 To 1500 g of the basic aluminum lactate solution of Example 1, 348.4 g of acrylic acid was added, and then 392.3 g of 25% aqueous ammonia was added at a temperature of 35° C. to obtain an aluminum acrylate composition (aluminum acrylate 17.5%, pH=7.1). The obtained aluminum acrylate composition was stable without precipitation even after 3 months at 40° C.

[0037] Example 3 To 1500 g of the basic aluminum lactate solution of Example 1, 348.4 g of acrylic acid was added, and then 502.2 g of 25% aqueous ammonia was added at a temperature of 35° C. to obtain an aluminum acrylate composition (aluminum acrylate 16.7%, pH=9.2). The obtained aluminum acrylate composition was stable without precipitation even after 3 months at 40° C.

[0038] Example 4 The aluminum hydroxide gel washed in Example 1 was placed in a 1L separable flask, 50% gluconic acid was added thereto, and the mixture was heated at 100°C for 2.5 hours to obtain 1750g of basic aluminum gluconate solution (Al2O3=4.0%, molar ratio of gluconic acid / Al2O3: 2.0). 73.1g of acrylic acid was added to this solution (temperature 25°C) to obtain an aluminum acrylate composition (aluminum acrylate 4.5%, pH=3.3). The obtained aluminum acrylate composition was stable without precipitation even after 3 months at 40°C.

[0039] Example 5 604.8g of water was added to a 3L separable flask and stirred at 200 rpm, and a mixed solution of 432.9g of aluminum sulfate aqueous solution (Al2O3 equivalent = 8.0%), 160.3g of sodium aluminate aqueous solution (Al2O3 equivalent = 20.0%), and 46.1g of 99% sodium carbonate was added thereto at the same time to obtain 1244.1g of aluminum hydroxide gel dispersion. At this time, the temperature was 15-20℃ and the pH was 6.5-7. The obtained gel dispersion was centrifuged at 2000 rpm x 1 minute with a centrifuge (Kansai Centrifugal Separator Manufacturing Co., Ltd. KBS-12), and the gel was washed three times with 4L of water, and then the gel was placed in a 1L separable flask, 90% lactic acid was added thereto, and the mixture was heated at 90℃ for 3.5 hours to obtain 1500g of basic aluminum lactate solution (Al2O3 = 8.1%, lactic acid / Al2O3 molar ratio: 2.0). 147.9 g of acrylic acid was added to this solution (temperature: 25° C.) to obtain an aluminum acrylate composition (aluminum acrylate 10.1%, pH=3.2). The obtained aluminum acrylate composition was stable without precipitation even after 3 months at 40° C.

[0040] Comparative Example 1 678.6 g of water was added to a 3 L separable flask and stirred at 200 rpm, and 314.7 g of an aqueous aluminum chloride solution (Al2O3 equivalent = 10.0%) and 250.8 g of an aqueous sodium aluminate solution (Al2O3 equivalent = 20.0%) were added thereto at the same time to obtain 1244.1 g of an aluminum hydroxide gel dispersion. At this time, the temperature was 25 to 30 ° C, and the pH was 9.5 to 10.5. The obtained gel dispersion was centrifuged at 2000 rpm x 1 minute with a centrifuge (Kansai Centrifugal Separator Manufacturing Co., Ltd. KBS-12), and the gel was washed three times with 4 L of water, and then the gel was placed in a 1 L separable flask, 90% lactic acid was added thereto, and the mixture was heated at 100 ° C for 2.5 hours, but a large amount of unreacted residue was generated and a basic aluminum lactate solution was not obtained.

[0041] Comparative Example 2 An aluminum acrylate composition (aluminum acrylate 16.6%, pH=2.9) was obtained by adding 259.5 g of acrylic acid to 1500 g of the basic aluminum lactate solution of Example 1 (temperature: 25° C.). The obtained aluminum acrylate composition precipitated and became cloudy after 3 days at 40° C.

[0042] Comparative Example 3 The aluminum hydroxide gel washed in Example 1 was placed in a 10L separable flask, water and 90% lactic acid were added thereto, and the mixture was heated at 100°C for 2.5 hours to obtain 5040g of an aluminum lactate solution (Al2O3=2.5%, lactic acid / Al2O3 molar ratio: 5.5). 42.3g of acrylic acid was added to this solution (temperature 25°C) to obtain an aluminum acrylate composition (aluminum acrylate 0.9%, pH=2.0). The obtained aluminum acrylate composition precipitated and became cloudy after 1 week at 40°C.

[0043] Comparative Example 4 To 1500 g of the basic aluminum lactate solution of Example 1, 348.4 g of acrylic acid was added, and then 672 g of 25% aqueous ammonia was added at a temperature of 35° C. to obtain an aluminum acrylate composition (aluminum acrylate 15.6%, pH=10.6). The obtained aluminum acrylate composition gelled after 3 days at 40° C.

[0044] As the material components and information obtained in the examples and comparative examples, the amount of aluminum acrylate, pH, the amount of aluminum converted into Al2O3, the amount of acrylic acid, the amount of hydroxy acid, and the amount of alkali component are shown in Table 1. Table 1 also shows the molar ratios of the aluminum molar amount converted into Al2O3 [A], the hydroxy acid molar amount [B], the acrylic acid molar amount [C], and the alkali molar amount [D]. The aluminum hydroxy acid is also shown as I / II, which is the ratio of the hydroxy acid molar amount (I) in the aluminum hydroxy acid to the Al2O3 molar amount (II) converted from the aluminum molar amount in the aluminum hydroxy acid. The pH value was measured at 20°C using a portable pH meter HM-40P manufactured by Toa DKK Corporation. Table 1 also shows the results of the evaluation of the appearance of the obtained aluminum acrylate composition after leaving it at 40°C for 3 months, as described below.

[0045] The appearance after 3 months at 40°C was visually observed and reported in Table 1 according to the following criteria: ○: No turbidity, no change. △: Slightly cloudy. ×: Precipitation and sedimentation occurred.

[0046] The method for calculating the mass percentages of acrylic acid, hydroxy acid (lactic acid), and alkali components in Table 1 will be described below. The mass% of acrylic acid, hydroxy acid (lactic acid) and alkali component in the case of Example 1 is calculated. Since 151.5g of acrylic acid is added, 151.5 / (151.5+1500g)×100=9.17% by mass, which is rounded off to 9.2% by mass. Regarding hydroxy acid (lactic acid), since "basic aluminum lactate solution 1500g (Al2O3=8.4%, lactic acid / Al2O3 molar ratio: 2.0)", the actual number of moles of lactic acid is 2.47 moles, and the amount of lactic acid is 2.47 moles × molecular weight of lactic acid 90=222.3g, and the mass% is 222.3÷(1500g+151.5g)×100=13.46% by mass, which is rounded off to 13.5% by mass. In Example 1, no alkali component is used, so the mass% of the alkali component is 0.

[0047] In the case of Example 1, the number of moles of aluminum [A] is 1.235 moles. The number of moles of hydroxy acid (lactic acid) [B] is 2.47 moles. The number of moles of acrylic acid [C] is 151.5 g ÷ 72 (molecular weight) = 2.10 moles. Therefore, [B] / [A] = 2, and [C] / [A] = 1.7. [D] is 0, so [D] / [A] = 0.

[0048] In the case of Example 2, the alkaline component is "392.3 g of 25% ammonia water", so 98.075 g is ammonia. Since 98.1 g of ammonia is contained in 1500 g of aluminum lactate aqueous solution and 348.4 g of acrylic acid, 98.1 ÷ (1500 + 348.4 + 392.3) × 100 is 4.37 mass%, rounded off to 4.4 mass%. The calculations for other Examples and Comparative Examples are similar to those above, and the results are as shown in Table 1.

[0049] [Table 1]

[0050] Example 6 A coating liquid was prepared by adding 30 parts of the aluminum acrylate composition obtained in Example 1 to 100 parts of polyethylene glycol dimethacrylate (commercially available as "9G" from Shin-Nakamura Chemical Co., Ltd.) and adding 0.5 parts of a 20% methanol solution of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (Omnirad 2959; manufactured by IGM Resins) as a photopolymerization initiator.

[0051] Dust-free paper (EX Clean EX72A4, manufactured by Sakurai Co., Ltd.) was cut into the shape of a JIS K7139 small tensile test piece a) type CW, and the coating liquid was applied to a thickness of 90 μm using a bar coater. The coating was then cured by irradiating with ultraviolet (UV) rays from a metal halide lamp for 10 minutes, and allowed to stand in a desiccator for 24 hours to obtain an initial sample piece.

[0052] The initial test pieces obtained were subjected to a tensile test at 5 mm / sec (1 level, n=3) using a tensile tester (manufactured by MinebeaMitsumi Inc.) to measure the maximum stress value (N). Next, the test pieces were left to stand for 7 days at a relative humidity of 70% RH, and then a tensile test was performed at 5 mm / sec using the same tensile tester (1 level, n=3) to measure the maximum stress value. The initial maximum stress value and the maximum stress value after the 7-day humidity environment test are shown in Table 2. Table 2 also shows the rate of decrease (%) of the maximum stress value for both maximum stress values, which is expressed by the following formula: Decrease rate of maximum stress value (%) = 1 - (maximum stress value of test piece left at 70% RH for 7 days / maximum stress value of initial test piece) x 100

[0053] The coating thickness of the initial test piece and the test piece after the 7-day humidity environment test was measured with a digital caliper, and the variation in coating thickness (%) was calculated using the following formula. The results are shown in Table 2. Film thickness variation (%) = 1-(minimum film thickness of test piece left for 7 days at 70% RH / maximum film thickness) x 100

[0054] (Comparative Examples 5 to 8) Instead of 30 parts of the aluminum acrylate composition obtained in Example 1 in Example 6, the following materials were added to prepare a coating liquid (Comparative Example 8 used only polyethylene glycol dimethacrylate). The amounts added were 5 parts of basic aluminum acrylate in Comparative Example 5, 30 parts of a 35% aqueous solution of magnesium acrylate in Comparative Example 6, 30 parts of a 25% aqueous solution of calcium acrylate in Comparative Example 7, and 100 parts of polyethylene glycol dimethacrylate in Comparative Example 8. The basic aluminum acrylate used in Comparative Example 5 was prepared by reacting aluminum sulfate with sodium acrylate in an aqueous solvent, washing the resulting hydrate with water and filtering, and drying the resulting solid, followed by dry-pulverization. Comparative Example 5: Basic aluminum acrylate (powder) Comparative Example 6: 35% magnesium acrylate aqueous solution Comparative Example 7: 25% aqueous calcium acrylate solution Comparative Example 8: Polyethylene glycol dimethacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product number "9G")

[0055] Using the obtained coating liquid, the maximum stress value, the rate of decrease (%), the film thickness and its variation (%) were measured in the same manner as in Example 6. The results are shown in Table 2.

[0056] [Table 2]

[0057] As shown in Table 1, in Examples 1 to 5, by controlling various molar ratios including the amount of aluminum in terms of Al2O3, the amount of acrylic acid, the amount of hydroxy acid, and the amount of alkali component of the present invention, it was confirmed that a stable solution can be obtained in a wide pH range even after 3 months at 40°C. On the other hand, in Comparative Example 1, the aluminum hydroxide gel was prepared in a high range of pH 9.5 to 10.5, and basic aluminum lactate, which is the precursor of the aluminum acrylate composition of the present invention, could not be synthesized. In Comparative Example 2, the ratio [C] / [A] of the mole number [C] of acrylic acid to the mole number [A] of aluminum was 2.9, which caused instability and precipitation. In Comparative Example 3, the lactic acid ratio of the precursor basic aluminum lactate was set outside the range of lactic acid / Al2O3 molar ratio: 5.5, which similarly caused instability and precipitation. In Comparative Example 4, the final pH was set high at 10.6, which was outside the range of the present invention, and caused instability and gelation.

[0058] As shown in Table 2, by adding the aluminum acrylate composition obtained in Example 1 of the present invention to a monomer and curing it with UV, the strength was improved, and the strength was not easily reduced even after a humidity test at 70% RH, and it was considered to be effective in water resistance. On the other hand, in Comparative Example 5, the strength decreased after the same humidity test, and white powder was observed on the film surface. This is because the powdered aluminum acrylate is insoluble and has low activity, so it is hardly incorporated into the paper base material or polymer. In Comparative Examples 6 and 7, the strength decreased after the same humidity test, and the film thickness changed. This is thought to be due to the extremely high hydrophilicity of the magnesium or calcium polymer and its property of swelling when hydrated. In the case of Comparative Example 8, when only the base resin was used, the strength also decreased after the same humidity test. Therefore, the effectiveness of the aluminum acrylate composition of the present invention as a functional agent for improving strength and water resistance was confirmed.

[0059] The aluminum acrylate composition of the present invention has excellent stability over a wide pH range of from 3 to 10, and when coated on paper and cured, can improve the strength and water resistance. [Industrial Applicability]

[0060] As described above, the product of the present invention can provide functions such as improving the water resistance of paper. In addition to metal cross-linking using aluminum ions, cross-linking with acrylic groups is also possible, making it possible to expand its applications to a wide range of fields. In addition, since it is possible to design the product to contain almost no corrosive inorganic acids or residual alkaline elements, it is expected to be used in life science and general industrial applications such as water-absorbent resins, water-containing gels, fibers, nonwoven fabrics, and cellulose, as well as functional additives for electronic materials such as semiconductor-related coatings and doping materials, sintered body binders, and alumina thin film formation.

[0061] The following aspects of the invention are added: [1] An aluminum acrylate composition comprising 1 to 35% by mass of aluminum acrylate and in the form of an aqueous solution having a pH in the range of 3 to 10, Aluminum is 2 to 15 mass% calculated as Al2O3, 2 to 30% by mass of acrylic acid, 4 to 25% by weight of a hydroxy acid, and Alkaline content: 0 to 15% by mass 1. An aluminum acrylate composition comprising: [2] The aluminum acrylate composition according to [1], wherein the hydroxy acid is at least one selected from the group consisting of lactic acid, gluconic acid and glycolic acid. [3] The aluminum acrylate composition according to [1] or [2], wherein the hydroxy acid is supplied in the form of an aluminum hydroxy acid, and the ratio of the number of moles of hydroxy acid in the aluminum hydroxy acid (I) to the number of moles of Al2O3 calculated from the number of moles of aluminum in the aluminum hydroxy acid (II) is in the range of I / II = 1.0 to 2.5. [4] The aluminum acrylate composition according to any one of [1] to [3], wherein the alkali component is at least one selected from the group consisting of monovalent alkali metals, ammonia, and water-soluble amines. [5] When the number of moles of aluminum in terms of Al2O3 in the aluminum acrylate composition is [A], the number of moles of hydroxy acid is [B], the number of moles of acrylic acid is [C], and the number of moles of an alkali component is [D], the following relational formula (1) or (2) is satisfied: (1) [B] / [A]=1.0~2.5, [C] / [A]=1.0~2.5, [D] / [A]=0, or (2)[B] / [A]=1.0~2.5, [C] / [A]=3.5~4.5, [D] / [A]=4.5~7.5 The aluminum acrylate composition according to any one of [1] to [4], wherein the ratio is within any one of the ranges above. [6] The method for producing an aluminum acrylate composition according to any one of [1] to [5], characterized in that an aluminum hydroxide gel is obtained by neutralizing an inorganic aluminum acid with an alkaline agent at a temperature of 0 to 40°C and a pH of 6 to 8, the aluminum hydroxide gel obtained is washed with water, and then a hydroxy acid is added to form an aluminum hydroxy acid, followed by addition of acrylic acid, and further adding an alkaline component as necessary to adjust the pH to 3 to 10. [7] The method for producing an aluminum acrylate composition according to [6], wherein the alkaline agent is at least one selected from the group consisting of sodium aluminate, sodium carbonate, ammonia and water-soluble amines. [8] The method for producing an aluminum acrylate composition according to [6] or [7], wherein the hydroxy acid is at least one selected from the group consisting of lactic acid, gluconic acid and glycolic acid. [9] The method for producing an aluminum acrylate composition according to any one of [6] to [8], wherein the alkali component is at least one selected from the group consisting of monovalent alkali metals, ammonia and water-soluble amines.

Claims

1. An aluminum acrylate composition comprising 1 to 35% by mass of aluminum acrylate and in the form of an aqueous solution having a pH in the range of 3 to 10, Aluminum is Al 2 O 3 Converted into 2 to 15 mass %, 2 to 30% by mass of acrylic acid, 4 to 25% by weight of a hydroxy acid, and Alkaline component: 0 to 15% by mass 1. An aluminum acrylate composition comprising:

2. 2. The aluminum acrylate composition according to claim 1, wherein the hydroxy acid is at least one selected from the group consisting of lactic acid, gluconic acid and glycolic acid.

3. The hydroxy acid is supplied in the form of aluminum hydroxy acid, and the number of moles of hydroxy acid (I) in the aluminum hydroxy acid and Al (I) calculated from the number of moles of aluminum in the aluminum hydroxy acid are 2 O 3 3. The aluminum acrylate composition according to claim 1, wherein the ratio of moles (II) of I to II is in the range of 1.0 to 2.

5.

4. 3. The aluminum acrylate composition according to claim 1, wherein the alkali component is at least one selected from the group consisting of monovalent alkali metals, ammonia and water-soluble amines.

5. The Al in the aluminum acrylate composition 2 O 3 When the number of moles of aluminum in terms of conversion is [A], the number of moles of hydroxy acid is [B], the number of moles of acrylic acid is [C], and the number of moles of an alkali component is [D], the following relational formula (1) or (2) is satisfied: (1) [B] / [A] = 1.0 to 2.5, [C] / [A] = 1.0 to 2.5, [D] / [A] = 0, or (2) [B] / [A] = 1.0-2.5, [C] / [A] = 3.5-4.5, [D] / [A] = 4.5-7.5 3. The aluminum acrylate composition according to claim 1, wherein the ratio of the aluminum acrylate to the aluminum acrylate is within the range of any one of the following:

6. 3. The method for producing an aluminum acrylate composition according to claim 1 or 2, characterized in that an aluminum hydroxide gel is obtained by neutralizing an inorganic aluminum acid with an alkali agent at a temperature of 0 to 40° C. and a pH of 6 to 8, the aluminum hydroxide gel obtained is washed with water, and then a hydroxy acid is added to form an aluminum hydroxy acid, followed by addition of acrylic acid, and if necessary, an alkali component is added to adjust the pH to 3 to 10.

7. 7. The method for producing an aluminum acrylate composition according to claim 6, wherein the alkaline agent is at least one selected from the group consisting of sodium aluminate, sodium carbonate, ammonia and water-soluble amines.

8. The method for producing an aluminum acrylate composition according to claim 6, wherein the hydroxy acid is at least one selected from the group consisting of lactic acid, gluconic acid and glycolic acid.

9. 7. The method for producing an aluminum acrylate composition according to claim 6, wherein the alkali component is at least one selected from the group consisting of monovalent alkali metals, ammonia and water-soluble amines.

Citation Information

Patent Citations

  • JP1973091012A

  • Hidorokishikiojusuru suiyoseikobunsho kakyozai

    JP1976081839A

  • (METH)acrylic acid metal salt composition

    JP1991131649A

  • Recording medium and image forming method using the same

    JP1996118788A

  • Recording medium and image forming method using the same

    JP1996174996A